2007
DOI: 10.31384/jisrmsse/2007.05.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FCI on Economic Growth in Pakistan

Abstract: The Two-Gap Model suggests that the Poor countries have to rely on the foreign capital inflows (FCI) to fill the two Gaps: Import-Export Gap and the Savings-Investment Gap. There are many forms of the foreign capital inflows like FDI (Foreign Direct Investment), External loans & Credit, technical assistance, Project & non-project aid etc. So, UDC's (including Pakistan) have to rely on the Foreign aid, Foreign Debts, FDI and portfolio investments. The role of these external resources (FCI) always remains questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…The impact of foreign inflows on poverty and economic development is found to be controversial in the literature. In some studies positive impact of foreign inflows was proved on poverty and economic development, while other studies highlighted its negative effects [Mohey-ud-din (2006)]. In case of Pakistan there are only few studies on the relationship between inflows and poverty, for example Siddiqui, et al (2006), Zaman, et al (2008) and Mohey-ud-din (2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of foreign inflows on poverty and economic development is found to be controversial in the literature. In some studies positive impact of foreign inflows was proved on poverty and economic development, while other studies highlighted its negative effects [Mohey-ud-din (2006)]. In case of Pakistan there are only few studies on the relationship between inflows and poverty, for example Siddiqui, et al (2006), Zaman, et al (2008) and Mohey-ud-din (2006).…”
Section: Introductionmentioning
confidence: 99%
“…In some studies positive impact of foreign inflows was proved on poverty and economic development, while other studies highlighted its negative effects [Mohey-ud-din (2006)]. In case of Pakistan there are only few studies on the relationship between inflows and poverty, for example Siddiqui, et al (2006), Zaman, et al (2008) and Mohey-ud-din (2006). After thorough literature review and analysis, these authors have explained the relationship between foreign inflows and poverty but none of them have computed the extent of the impact between the two variables.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Shahbaz and Rahman (2012) concluded in a study that imports play a crucial role between exports and economic growth, and ignoring imports from the analysis can yield misleading results (Mohey-ud-Din, 2007). A large share of imports of developing countries consists of capital and intermediate goods which enter into domestic production; so imports expand the country"s production possibilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main argument supporting the hypothesis is that sound intermediaries in a proper regulatory framework ends up boosting saving and capital accumulation. Capital formation is the one important determinant of 4 Studies found positive impact of foreign aid on economic growth (Shabir and Mahmood, 1992;Mohey-ud-din, 2006), while others argued that foreign aid inversely impacted Pakistan economic growth (Khan and Ahmed, 2007;Ali, 1993;and Khan and Rahim, 1993;Javed and Qayyum, 2011). 5 Mckinnon (1973) and Shaw (1973), King and Levine (1993), Beck et al, 2000a, Abu-Bader andAbu-Qarn (2008),among others investment and hence of economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Macroeconomic impact of foreign aid is also controversial in case of Pakistan. A few studies found positive impact of foreign aid on economic growth in case of Pakistan (Shabir and Mahmood, 1992;Mohey-ud-din, 2006).Some studies found that foreign aid inversely affected the economic growth (Ali, 1993;Khan and Rahim, 1993;Ishfaq and Ahmed, 2005;Khan and Ahmed, 2007). Javed and Qayyum (2011) have investigated the role of macroeconomic policy in aid effectiveness in case of Pakistan.…”
Section: Review Of Literaturementioning
confidence: 99%